SI-Kepo Workshop: Hybrid Training in Scientific Writing for Raden Rahmad Mojosari Vocational School Educators - Darmayanti, Rani; Hariyadi, Ahmad; Choirudin; Kurniawati, Wiwit; Anggraini, Dian (CV. BImbingan Belajar Assyfa, 2024)
This community service activity aims to improve the knowledge and skills of teachers at Raden Rahmad Mojosari Vocational School in Mojokerto, East Java in writing scientific papers. This training program, called SI-Kepo Workshop, combines online and offline sessions to provide an understanding of how to create a Google Scholar account, write scientific articles, and submit manuscripts to national journals. The training includes theoretical explanations and practical assignments tailored to the interests of the participants. The results of the training showed a significant increase in the knowledge and skills of participants in preparing and submitting scientific articles. However, the effectiveness of writing still needs to be improved through ongoing and more structured training programs. It is hoped that this training can be the beginning of a routine program that focuses on teacher professional development in scientific writing.